Keefektifan Bimbingan Kelompok Teknik Problem Solving dalam Mencegah Perilaku Bullying Pada Siswa SMAN 1 Kuala Kampar - Khairul Dwi Pangestu; Akhmad Fajar Prasetya (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Bullying is described as antagonistic behavior, both physical and verbal, that is frequently demonstrated by someone. The purpose of bullying behavior is to gain acceptance from others. Bullying often occurs regularly, and in some cases, even organized. Bullying has a negative impact on its victims, including depression and trauma, which can disrupt their psychology and even their mental and physical health. This research uses quantitative methodology. Quantitative research is a method of gathering knowledge that uses numerical data to analyze information about a subject of interest. Because the quasi experimental research technique is a component of a quantitative approach with unique characteristics that are not coincidental, the existence of a control group was used in this research. In this research, all topics as they have been developed organically in class are used. There are two classes in this method: control class and experimental class.